Fish out of Water: Translation, Legitimation, and New Venture Creation - Tracey, Paul; Dalpiaz, Elena; Phillips, Nelson (Academy of Management Journal, 2018)
We draw on institutional theory to study a common type of new venture creation that has been neglected in the literature: the translation of an existing organizational form from a different—and misaligned—institutional context. To do so, we conducted an in-depth case study of H-Farm, an Italian venture that was founded as a business incubator, a type of organization that first emerged in Silicon Valley and other U.S. technology regions. Our study illuminates the specific configuration of legitimacy pressures inherent in this type of entrepreneurship, and theorizes the strategies that entrepreneurs can enact to address them: local authentication work, category authentication work, and dual optimal distinctiveness work. We also show that the legitimacy pressures experienced by entrepreneurs may vary significantly as ventures mature, and challenge the notion of a specific “legitimacy threshold” that new ventures are required to reach. Finally, our model conceptualizes translation as an iterative, dynamic, and ongoing accomplishment rather than a “one off” activity with clear beginning and end points.